Development and remote management of projects using virtual methodologies in times of Covid-19: Case study in the industrial pole of Manaus, state of Amazonas, Brazil - Kieling, Antonio Claudio; Barboza, Ricardo da Silva; Oliveira, Raymond Correa de; Junior, Jucimar Maia da Silva; Silva, Gabriel de Lima e; Lins, Rafael Dueire; Bernardino, Rodrigo Barros; Silva, Emmerson Santa Rita da; Junior, Acursio Ypiranga Benevides (Seven Editora, 2023)
The Covid-19 pandemic has forced the use of means of interaction and project management in an iterative and non-face-to-face manner. Virtual interaction and monitoring tools were evidenced as a solution in this context. The legislation requires companies that manufacture computer goods in the region of the Manaus Free Trade Zone (ZFM), Amazonas, Brazil, to invest part of their revenues in Research, Development and Innovation (RD&I) activities. A project to create and develop applications for means of payment via card was executed through the joint action of Science and Technology Institutions (ICTs) in the Industrial Pole of Manaus (PIM) between University of the State of Amazonas (UEA), Federal University of Amazonas (UFAM) and Federal Institute of Amazonas (IFAM). Resources such as Google Meet, Jamboard, Scrum, Git, GitHub, GitHub Classroom, GitKraken, Google Sheets, Android Studio, Information Architecture, UML enabled the collective virtual work not in person between research professors and scholarship students in the development of 15 Android applications, allowing various sectors of the economy to manage their business in the palm of their hand. DOI:https://doi.org/10.56238/emerrelcovid19-025